Efek Antiproliferatif Ekstrak dan Fraksi Daun Mahoni pada Sel Hela - Sari, Diah Komala; Arifah, Nur; Widayanti, Gusti Ayu (Poltekkes Kemenkes Palembang, 2025)
Background: Cervical cancer is one of the leading causes of death among women, particularly in developing countries. The development of anticancer agents from natural sources such as mahogany leaves (Swietenia mahagoni (L.) Jacq.) continues to attract research interest due to their promising potential. This study aimed to evaluate the antiproliferative effects of ethanol extract and bioactive fractions of mahogany leaves on cervical cancer (HeLa) cells in vitro. Methods: This research employed an experimental quantitative approach. Mahogany leaves were extracted using ethanol and further fractionated with n-hexane, ethyl acetate, and ethanol-water. Cell viability was assessed using the MTT assay and an ELISA reader at a wavelength of 550 nm. Antiproliferative activity was determined by measuring cell doubling time after treatment using ½ IC₅₀ concentration of the active fraction. The phytochemical constituents in the active fraction were identified through thin-layer chromatography (TLC). Results: The ethyl acetate fraction exhibited significant antiproliferative activity with a doubling time of 59 hours, compared to 34 hours in the control group and 81 hours with cisplatin. Absorbance values at 72 hours were also lower than the control, indicating suppressed cell proliferation. Phytochemical analysis identified the presence of flavonoids, saponins, and limonoids as major bioactive candidates. Conclusion: The ethyl acetate fraction of mahogany leaf extract demonstrates antiproliferative activity against HeLa cells and shows potential for development as a natural anticancer agent.